Strategi Pemasaran Digital Dalam Mengatasi Persaingan Bisnis - Octivaningsih, Arum Rakhmasari; Novedliani, Riztrya; Muslimin, Mohammad; Ma'sum, Hadiansyah; Wahyuni, Ritna (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The purpose of this study is to determine the effectiveness of digital marketing strategies in overcoming business competition. This research approach collects data through literature studies, which involve reading literature from various sources including books, articles, journals and reports using qualitative and deductive approaches. The findings in this study are that digital marketing strategies are effective strategies to overcome increasingly tight business competition. By optimizing SEO, social media marketing, content marketing, paid advertising, email marketing, retargeting and remarketing, as well as performance analysis and measurement, a company can win the competition in today's digital era. Companies that are able to adapt to digital trends and use the right marketing strategies will have a competitive advantage and be able to survive in a dynamic market.